Spectroscopic studies of SnO2 doped with Cr, Co or Nb - Brankovic, G. [UNESP]; Brankovic, Z. [UNESP]; Santos, L. P S; Longo, Elson [UNESP]; Davolos, Marian Rosaly [UNESP]; Varela, José Arana [UNESP] (Trans Tech Publications, 2003)
SnO2 ceramics doped with different amounts of Co, Cr or Nb were investigated using visible and infrared spectroscopy at room temperature. Based on the observed d-d transitions the valence states of incorporated dopants were determined. Values of the optical band-gap were calculated in all samples. The infrared spectra of the samples displayed variations in the position, relative intensity and width of the bands, which were attributed to the presence of dopants.
Keywords: Dopants; Electronic structure; IR; Tin oxide; Visible spectroscopy; Optical band gap; Valence states; Calcination; Ceramic materials; Chromium; Cobalt; Electron transitions; Energy gap; Infrared spectroscopy; Mortar; Niobium; Oxides; Powders; Tin compounds